Using Text-Based Materials to Improve English Listening Skill of Elementary Students - Yuli Kuswandari (Universitas Ahmad Dahlan, 2018)
ABSTRACTThis research aimed to improve English listening skill through text-based materials at the grade V students of SD Muhammadiyah Kedungbanteng II. This was a classroom action research, which used the cycle model of Kemmis and McTaggart (2000), consisting of three steps, (1) plan, (2) act and observe, and (3) reflect. The research instruments were observation, fieldnote, interview, and listening tests. The reliability of the data was obtained by using the triangulation method. The data were analyzed by using an interactive model developed by Miles and Hubberman (1984). The results of the research showed that the English listening skill of students improved by using text-based materials. Based on the process, the students’’ attention to the classroom activities improved and they enjoyed all classroom activities well. From the product of listening, the improvement can be seen from the result of students’’ listening test. The mean score of the pre-action test is 55.05, while the mean score of the post-action test is 76.1. Keywords: text-based materials, listening skill